Post‐Transplant Recurrence of Focal Segmental Glomerulosclerosis in a Child With Heterozygous Mutations in NPHS1 and NPHS2. Issue 3 (June 2016) - Battelino, Nina; Arnol, Miha; Kandus, Aljoša; Ponikvar, Rafael; Novljan, Gregor
Abstract: Renal transplantation is the optimal renal replacement therapy (RRT) in children, but some primary diseases can recur after transplantation, and recurrence accounts for a significant proportion of graft losses, being second only to acute rejection. The risk of disease recurrence is highest among patients with idiopathic focal segmental glomerulosclerosis (FSGS), presumably due to a circulating permeability factor. Less is clear about the genetic forms of FSGS, where the data regarding the frequency of recurrence are rather conflicting. We present a 12‐year‐old girl with rapidly progressive FSGS and end‐stage renal disease in her native kidneys associated with heterozygous mutations in NPHS1 and in NPHS2, suffering from early post‐transplant recurrence. On the basis of reviewed literature, and until further and more conclusive evidence considering pathogenicity is provided, we propose that FSGS patients with heterozygous mutations in NPHS1 or NPHS2 should be considered as having idiopathic FSGS, and post‐transplant recurrence should be anticipated.